1996
DOI: 10.1103/physrevb.53.1779
|View full text |Cite
|
Sign up to set email alerts
|

Two-center two-electron excitations identified in NEXAFS for solid Ne

Abstract: REPORT DOCUMENTATION PAGEForm Aoved PIO( t O'l'ft l b..dtn tfo tlhsi cQIIeCOn 0 flIO rmatO,|o-estin*atro to a (verge I hour tponje• including the timc ot recviewing in t.uction. seta(Ching exq sinst gt dA a $Out(,, g14ther'*n O .14 antn~ n the data needed. And Cinplt elmtg and tev.€i *ng the QI1CCUen or i* .taon. S cnd (onment$ Aiedgdrnq this burden cisrt imt, 0 any other jS•p(t O0 th,.s collec'.o. of nIlor. At.On. nc:lud-mg S.ggetiOns 10, r ,educing this b cden. Experimental K-edge NEXAFS (near edge X-ray abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…Recent work 19 also shows that the Ni atoms primarily have actual charge of +2 for all oxidation states. We utilized the Hedin−Lundquest potential, which we find, consistent with previous experience, gives the best agreement with experiment. The maximum path length was set to 8−10 Å for the one- and two-shell calculations and to 15 Å for the nine-shell calculations.…”
Section: Experiments and Theorysupporting
confidence: 70%
See 2 more Smart Citations
“…Recent work 19 also shows that the Ni atoms primarily have actual charge of +2 for all oxidation states. We utilized the Hedin−Lundquest potential, which we find, consistent with previous experience, gives the best agreement with experiment. The maximum path length was set to 8−10 Å for the one- and two-shell calculations and to 15 Å for the nine-shell calculations.…”
Section: Experiments and Theorysupporting
confidence: 70%
“…We have previously 20-22 performed FEFF6 calculations on alkali halides and condensed rare gases (particularly Ne) to test the validity of this code and found that the code reproduces almost all of the experimentally observed peaks except the highly localized excitonic peaks very near or below the edge. For the first-row transition metals and lighter elements, the absolute energy must be shifted by 0−5 eV for optimum agreement with experiment. Here, the FEFF6 results were optimally aligned with the experimental data for Ni(OH) 2 , and then the FEFF6 results for NiOOH and BaNiO 3 were shifted by the identical amount.…”
Section: Experiments and Theorymentioning
confidence: 76%
See 1 more Smart Citation
“…Curved-wave−multiple-scattering (CW−MS) cluster calculations utilizing the FEFF6 code developed by Rehr and Albers , were performed in this work. We have previously , performed FEFF6 calculations on alkali halides and condensed rare gases to test the validity of this code and found that the code reproduces almost all of the experimentally observed peaks except the highly localized excitonic peaks very near or below the edge (particularly for Ne). For the first row transition metals and lighter elements, the absolute energy must be shifted by 0−5 eV for optimum agreement with experimentally observed results.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…Pure rare gas matrices 10.1.1. Solid Neon A number of workers have used X-ray absorption spectroscopy to study solid neon, with the emphasis on understanding the one and two electron processes occurring in the NEXAFS/XANES region [220][221][222][223][224][225][226], rather than the structural information in the EXAFS part of the spectrum. Complementary resonant X-ray absorption experiments of neon clusters with 15-4000 atoms in molecular beams have been carried out [227,228] as have calculations using improved coupled cluster techniques [229].…”
Section: Xafs Studies Of Matrix Structures and Guest-host Interactionsmentioning
confidence: 99%